Electrothermal Actuator on Graphene Bilayer Film. Issue 12 (17th October 2017) - Sang, Wei; Zhao, Liming; Tang, Rong; Wu, Yeping; Zhu, Chunhua; Liu, Jian
Abstract: Electrodriven bilayer actuator is designed and fabricated by spin‐coating a reduced graphene oxide solution onto a polymer substrate. The bonded interface properties, electrical and thermal conductivities are characterized through scanning electron microscopy and X‐ray diffraction. The bilayer actuator exhibits fast and large bending response when a direct current voltage is applied to the graphene layer. Whereas it exhibits oscillation when an alternating current voltage is applied to the bilayer actuator. The effects of the layer structure and the electro‐operation methods on the bending motions are studied. Two new actuation modes are explored to broaden the applications of electrodriven bilayer actuator, which are achieved by the actuator structure design and the driven current control. Electrically responsive graphene bilayer soft actuator provides the potential applications in the fields of thin‐film electronics, sensors, and energy conversion. Abstract : Electric current generated Joule heating on a graphene bilayer film subsequently results in the expansion and bending of the bilayer film, which achieves electrical‐to‐mechanical energy transition of a smart actuator. Various actuation modes are demonstrated by the bilayer structure design and the electric current controlling.